Can digital financial inclusion promote the nighttime economy? - New evidence from Chinese counties’ nighttime lighting data and threshold model - Chen, Lei; Du, Tao; Wu, Difan; Lai, Chengrui (Technological and Economic Development of Economy, 2024)
In the post-pandemic era, the relative weakness of the economy is reflected not only in the macro data but also in the nighttime economy. Based on the threshold model and unbalanced panel data of 1772 county-level administrative units in China from 2014 to 2020, this paper deeply explores the relationship between digital inclusive finance and night economy and draws the following conclusions. (1) When digital financial inclusion exceeds certain thresholds, its beneficial influence on promoting the nighttime economy increases from 8.13% to 26.59% and 87.71%. (2) Digital financial inclusion promotes the nighttime economy by increasing employment in the secondary industry and promoting technological innovation. However, digital financial inclusion hinders the nighttime economy by reducing entrepreneurial activity in the accommodation and catering sectors. (3) Coverage breadth first inhibits, then promotes, and inhibits the nighttime economy in different intervals; the effect of usage depth and digital level on the nighttime economy in intervals shows an increasing trend. (4) In the Yangtze River Economic Belt region, digital financial inclusion initially inhibits the nighttime economy but turns into promotion as it develops; after the implementation of the rural revitalization strategy in 2017, digital financial inclusion can more positively and significantly promote the nighttime economy.